Communicative activities to improve students speaking in the tenth grade G in the Ciudad de Cuenca High School - Vele Fernández, Mirian Lorena
This project was developed to improve my students´ speaking and fluency during the English classes. It is clear that if they can communicate with their classmates then they will get a good understanding. My work is focused on the students of the tenth grade "G" of the Ciudad de Cuenca" High School. A common characteristic among these students is that they feel ashamed when they have to speak in English. They think that they cannot pronounce any word correctly and consequently they have serious limitations in their oral skill; and this blocks any progress in mastering the language. My hypothesis of work was based on the Humanistic theory from Erick Erikson and Abraham Maslow whom studied the influence of culture and society in the teenagers´ growth. They mean that encouragement, as certain other activities will help to accelerate the acquisition of a L2. This hypothesis proved that, encouragement as speaking activities would transform in valuable tools in order to increase the studentsï learning. It means that when they work together in the learning of a L2, they will speak in English. It is because they are not trying to speak English in front of the class, but they will be able to speak in English if they work in pairs, groups or among all students, and that does not matter if they make mistakes. Therefore, they will not feel ashamed anymore